Digital Learning Media in Learning to Write Poetry for Middle School Students - Taufik, Taufik; Ismail, Ismail; Imansyah, M. Nur; Putri Kasmita, Mayang (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Research has been carried out entitled Digital Learning Media in Learning to Write Poetry for Middle School Students. This research aims to determine the influence of digital learning media on the learning outcomes of class VIII students at SMPN 02 Woja. This type of research is quantitative research using the Quasi Experimental Design method, especially the non-equivalent control group design type. From the learning results obtained before treatment, both the experimental class and the control class showed the same abilities. Next, the posttest value data was tested. The results of the posttest analysis show that the average score for the experimental class is 51.21, while the average score for the control class is 41.70. Based on inferential statistical analysis of the posttest scores, it was found that the calculated t value (t_count) was 1.99 greater than the t table value (t-table) of 1.669. This shows that H0 (null hypothesis) is rejected and H1 (alternative hypothesis) is accepted.